Governance Challenges and the Impact of Corruption on Socio-Economic Stability: A Literature Study in Developing Countries - Akhtar, Rana Sharjeel; Hakim, Muh. Adrikni Al; Dewi, Lutfiani Puspita; Nuryana, Ita; Nihayah, Dyah Maya (Universitas Negeri Semarang, 2025)
Corruption is one of the most serious challenges in governance and business, especially in developing countries like Indonesia. The impact is not only limited to the state's financial losses, but also undermines public confidence and hampers socio-economic stability. This study aims to systematically examine how corruption impacts governance, public trust, and economic stability through the Systematic Literature Review (SLR) approach. The literature was collected from various databases of leading international journals, applying strict inclusion and exclusion criteria to ensure the relevance and quality of the empirical evidence. The synthesis results show that corruption hurts public policy effectiveness, reduces resource allocation efficiency, and deepens social inequality. The study also found that weak supervision, low transparency, and overlapping regulations are the root of problems in governance, especially in the State-Owned Enterprises (SOEs) sector. Thus, eradicating corruption and improving sustainable governance are key to rebuilding public trust and supporting inclusive economic development. These findings are expected to make a conceptual contribution to the development of anti-corruption policies in developing countries.